2019
DOI: 10.1177/1055665619888308
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustments Among Adolescents With Craniofacial Conditions and the Influence of Social Factors: A Multi-Informant Study

Abstract: Background: Previous studies have investigated psychosocial adjustments among adolescents with cleft lip and/or palate (CL/P), but our understanding of other craniofacial conditions remains limited. The objective of this study is to compare psychosocial adjustments among 3 groups of adolescents: craniofacial conditions other than cleft lip and/or palate (craniofacial anomaly [CFA]), CL/P, and controls (CON). Our secondary objective is to examine how social factors may predict the adjustments levels. Design: Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 79 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…19 Previous research conducted amongst adolescents with craniofacial anomaly have suggested that this group may be at an increased risk of experiencing psychosocial difficulties . 24 Our findings may, therefore, shed further light on how these difficulties may present at a younger age, and how consideration to these factors from early on in the patient's care may be important for supporting young people at later stages, and during adolescents. Further, the data reported in this study were limited to parent-report measures only.…”
Section: Discussionmentioning
confidence: 67%
“…19 Previous research conducted amongst adolescents with craniofacial anomaly have suggested that this group may be at an increased risk of experiencing psychosocial difficulties . 24 Our findings may, therefore, shed further light on how these difficulties may present at a younger age, and how consideration to these factors from early on in the patient's care may be important for supporting young people at later stages, and during adolescents. Further, the data reported in this study were limited to parent-report measures only.…”
Section: Discussionmentioning
confidence: 67%
“…Human behavior must fulfill three things, namely: 1) the intrinsic Islam that is knowing the concept of the caliph, knowing the concept of selfexcellence, knowing the mission, building a mission, creating insight, commitment, identity, intelligence, ideals , luck, creativity, obsession, and worship; 2) social attitudes and perspectives which include prejudice, mutual trust, mutual support, cooperation, openness, defensive, closed, withholding information (consisting of non-cooperative and down appearance), living principles (consisting of material capital and spiritual capital), experience (consisting of positive and negative), interests (consisting of long-term and long-term), wisdom based on the rules of Allah SWT and His Messenger, comparison (high value standards, low value standards, objective and subjective), and literature (consisting of religion, philosophy and science); and 3) da'wah and self-valuesas true faith and confidence, istikhlas, ihsan (tawajuh), ihtisab, mujahadah nafsi, sure in the sentence of thayyibah, special prayer, knowledge of ma'azikir, ikromul muslimin, tashihunniyat, and da'wah wa al-tabligh Sukenti, Tambak, & Charlina, 2020). Bous et al (2019) research findings show that psychosocial possessed by a person dramatically influences adaptation to the environment. Social factors are predicted to build relationships and attitudes of someone in implementing something new.…”
Section: The Influence Of Islamic Psychosocial On Learning Assessment Of Madrasah Aliyah Teachersmentioning
confidence: 99%
“…The social stigma associated with craniosynostosis deformities is an indication for repair, and prior studies have shown that children with craniofacial anomalies are at high risk for adverse psychosocial outcomes, primarily due to bullying from peers. 26,27 Our finding that patients who underwent OCVR were less likely to have a "normal" overall appearance has substantive implications for their mental health. The poor agreement between adolescent raters was likely due to the nature of the population surveyed.…”
Section: Discussionmentioning
confidence: 91%